Pyogenic Granuloma – A Common Benign Vascular Tumor with Variable Clinical Presentation: New Findings and Treatment Options - Wollina, Uwe (Open Access Maced J Med Sci, 2017)
Pyogenic granuloma is a common benign vascular tumour occurring in all ages. Both skin and mucous membranes can be affected. Of pathogenetic importance are trauma, BRAF mutations and probably herpes virus type 1, Orf virus and/or human papilloma virus type 2. The tumour consists of capillary proliferations, venules and fibromyxoid stroma. The development of a lesion occurs in three stages and bleeding is a common symptom. The tumour can mimic various other vascular lesions, solid tumours, and soft tissue infections. In recent years, targeted tumour therapies have become the most common cause of drug-induced pyogenic granulomas. The backbone of treatment is surgical procedures including laser therapy. New developments in medical drug therapy include topical and systemic beta-adrenergic receptor antagonists timolol and propranolol. Drug therapy is an alternative for young children, ocular and periungual pyogenic granuloma.